Manikya Bhasma as Nanomedicine for Cancer Cells Treatment and its Characterization Using Modern Scientific Tools - ., Reena; Sharma, Preeti; Jasuja, Nakuleshwar Dut; Kumar, Sunil (Asian Pacific Journal of Environment and Cancer, 2024)
Objective: This study is focused on evaluating the safety and effectiveness of Manikya Bhasma, an Ayurvedic preparation, as a nanomedicine for cancer treatment, and exploring its potential therapeutic properties using modern scientific tools. Methods: Manikya Bhasma, composed of purified ruby, orpiment, and arsenic sulfide, was analyzed using XRD (X-ray Diffraction) for crystallite size determination, FESEM (Field Emission Scanning Electron Microscopy) for morphological analysis, EDS (Energy Dispersive X-ray spectroscopy) for elemental composition, and FTIR (Fourier Transform Infrared Spectroscopy) for functional group identification. The anticancer activity of Manikya Bhasma nanoparticles was assessed against breast cancer (MCF-7) and lung cancer (A-547) cell lines at varying concentrations (0-1000 µg/mL). Results: The XRD analysis revealed an average crystallite size of 60 nm. FESEM micrographs confirmed the uniform distribution of particles within the sample. Notably, Manikya Bhasma demonstrated a clear dose-dependent anticancer activity against both MCF-7 and A-547 cell lines, providing reassurance about its potential effectiveness. Conclusion: This study suggests that Manikya Bhasma has the potential to be a promising nanomedicine for cancer treatment, highlighting the therapeutic relevance of traditional Ayurvedic medicine in modern scientific research. This research serves as a bridge between traditional and modern approaches, offering new insights into the application of Ayurvedic formulations in contemporary medicine.